The phonetic and phonological status of the r-phones in Tunisian Arabic - Oueslati, Jamila (Lingua Posnaniensis, 2017)
Some aspects of the participation of the r-phones in the phonetic and phonological systems of Tunisian Arabic are discussed against the background of a brief acquaintance with the situation obtaining in Standard Arabic and Classical Arabic. In contemporary Tunisian Arabic six r-phones occur and the relations of free variation, complementary distribution and phonological opposition between them are examined. The assimilation of the [r] to [l] is touched upon. The situation of r-phones in other Arabic dialects is addressed.